Система суб’єктів забезпечення реалізації прав громадян у сфері підприємницької діяльності в Україні - Леонов, О. О.; Leonov, O. O. (Наше право. - 2024. - № 1. - С. 339-345, 2024)
Виокремлено коло суб’єктів, які відповідають за забезпечення реалізації прав громадян у сфері підприємницької діяльності в Україні, а також надано характеристику їх адміністративно-правовому статусу. Запропоновано авторський підхід щодо класифікації відповідних суб’єктів.

It is argued that the system of subjects for ensuring the realization of citizens’ rights in the field of entrepreneurial activity in Ukraine is quite comprehensive and includes a number of holders of power with a special legal status that influence social relations that arise in this field. The scope of this system includes: 1) subjects whose activity in relation to ensuring the realization of citizens’ rights in the field of entrepreneurial activity is not the main one; 2) entities that have a branch orientation and are responsible for compliance with the legislation of the conditions of admission to certain types of business activity; 3) subjects in which the main functional purpose is to ensure the possibility of realizing the rights in question. It is emphasized that the administrative and legal status of the subjects of ensuring the realization of citizens’ rights in the field of entrepreneurial activity is a set of tasks, functions, and competences and powers provided for their performance. Its features are determined by the direct task that the legislator puts forward to the subject in the context of ensuring the realization of the right in question. Thus, in accordance with this criterion, it is proposed to divide the specified subjects into several groups: 1) those that provide legal regulation of the main issues of entrepreneurial activity, establishing universally binding rules of conduct in this area: the Verkhovna Rada of Ukraine, the President, the Cabinet of Ministers of Ukraine ; 2) who verify the compliance of citizens with the legally defined conditions of entrepreneurial activity and ensure the registration of the fact of a person’s initiative to engage in it; 3) which agree on special opportunities for conducting certain types of business (for example, the use of natural resources, obtaining licenses for certain types of activities); 4) subjects whose main purpose of activity is to facilitate the implementation of entrepreneurial activity; 5) entities that supervise and control the compliance of business activities with established conditions, in particular, countering unfair competition, etc.

Выделены круг субъектов, отвечающих за обеспечение реализации прав граждан в сфере предпринимательской деятельности в Украине, а также предоставлена ​​характеристика их административно-правового статуса. Предложен авторский подход к классификации соответствующих субъектов.
Keywords: адміністративно-правовий статус; суб’єкт; забезпечення; права громадян; підприємницька діяльність; administrative and legal status; subject; security; rights of citizens; entrepreneurial activity; административно-правовой статус; субъект; обеспечение; права граждан; предпринимательская деятельность